Effectiveness of ski and pole forces in ski skating - Smith, G.; Kvamme, B.; Jakobsen, V. (Science and Skiing IV, 2008)
INTRODUCTION: Distribution of workload across the legs and upper body can affect metabolic costs in skiing. Bellizzi et al. (1998) found that the cost of generating poling force is nearly 40 times the cost of generating force by the legs through the skis. In ski skating, the V1 and V2 techniques distribute workload differently through adjustments of force timing, magnitude, and direction. This study evaluated the effectiveness of propulsion deriving from skis and poles in these two skating techniques.